Regulatory Role of GRK2 in the TLR Signaling-Mediated iNOS Induction Pathway in Microglial Cells - Palikhe, Sailesh; Ohashi, Wakana; Sakamoto, Takuya; Hattori, Kohshi; Kawakami, Masaaki; Andoh, Tsugunobu; Yamazaki, Hiromi; Hattori, Yuichi (Frontiers in Pharmacology, 2019)
G protein-coupled receptor kinase 2 (GRK2) is a ubiquitous member of the GRK family that restrains cellular activation by G protein-coupled receptor (GPCR) phosphorylation leading to receptor desensitization and internalization, but has been identified to regulate a variety of signaling molecules, among which may be associated with inflammation. In this study, we attempted to establish the regulatory role of GRK2 in the Toll-like receptor (TLR) signaling pathway for inducible nitric oxide synthase (iNOS) expression in microglial cells. When mouse MG6 cells were stimulated with the TLR4 ligands lipopolysaccharide (LPS) and paclitaxel, we found that interferon regulatory factor 1 (IRF1) protein expression and activation was upregulated, transcription of interferon-β(IFN-β) was accelerated, induction/activation of STAT1 and activation of STAT3 were promoted, and subsequently iNOS expression was upregulated. The ablation of GRK2 by small interfering RNAs (siRNAs) not only eliminated TLR4-mediated upregulation of IRF1 protein expression and nuclear translocation but also suppressed the activation of the STAT pathway, resulting in negating the iNOS upregulation. The TLR3-mediated changes in IRF1 and STAT1/3, leading to iNOS induction, were also abrogated by siRNA knockdown of GRK2. Furthermore, transfection of GRK2 siRNA blocked the exogenous IFN-β supplementation-induced increases in phosphorylation of STAT1 as well as STAT3 and abrogated the augmentation of iNOS expression in the presence of exogenous IFN-β. Taken together, our results show that GRK2 regulates the activation of IRF1 as well as the activation of the STAT pathway, leading to upregulated transcription of iNOS in activated microglial cells. Modulation of the TLR signaling pathway via GRK2 in microglia may be a novel therapeutic target for treatment of neuroinflammatory disorders.